Acceptance of 21st century elements education among teachers in Malaysia - Nayan, Nasir; Mahat, Hanifah; Hashim, Mohmadisa; Saleh, Yazid; Kurniawan, Edi; Khotimah, Nurul (Institute of Advanced Engineering and Science, 2025)
Malaysia’s education development plan 2013-2025 promotes 21st-century learning. Instruction, learning, and school assistance are the key focus. This study selected Rompin State instructors to assess their 21st-century education ability, perspective, and application. The questionnaire was the main data-gathering tool in this quantitative investigation. Standard random sampling chose 152 school teachers. This study used Pearson correlation and t-test for descriptive and inferential analysis. The results showed reasonable knowledge, attitude, and practices (mean=2.95, standard deviation=0.22, 2.94, 0.23, 2.90, 0.29). The t-test showed significant differences in knowledge (t=-2.11, df=157, p 0.05) and attitude (t=-2.26, p 0.05) but not in practice (t=-1.81, p>0.05). Using Pearson correlation analysis, knowledge, and behaviors were moderately positively correlated (r=0.677, p<0.01), whereas attitudes and practices were strongly positively correlated (r=0.837, p<0.1). Teachers have modest knowledge, attitudes, and practices. Teachers must frequently take short courses to improve their 21st-century education. Mandatory authorities and scholars will help instructors professionally grasp 21st-century education. This study found that teachers with 21st-century education literacy can improve their knowledge, attitude, and practice and regularly apply it to their teaching.